(untitled) (Zaporizhzhia Historical Review, 2021)
The object of research are Zaporizhzhyan seals. Basing upon the research of archival and museum materials, the author concludes that according to the signatures, materials, techniques of production, placing in the document, functional destination, character of the document sealed etc. Zaporizhzhyan seals are equal to their compliances in Hetmanschyna.